Treatment of Organic Fertilizers And Inorganic On The Growth And Yield Of Mustrain Plants (Brassica Juncea L.) - Sembiring, Riduan; Sinaga, Robert; Sembiring, Swati; Karo, Seringena Br; Butar-Butar, Marselinus (Golden Ratio of Data in Summary, 2025)
Mustard plants are vegetables favored by people in Indonesia, they have nutritional value, are delicious, and are rich in protein, which is good and needed by the human body, vitamins A, B, and L-ascorbic acid. This study was conducted to determine the effect of organic, and inorganic fertilizers and their interaction on the growth and yield of mustard plants, carried out at UPTD. BIHedung Johor Medan, October 2023 to January 2024. Using RAK factorial 2 factors, I. dosage Organic fertilizer (organic) (A) 4 levels: A0 = 0 kg/plot (control), A1 = 1.5 kg/plot, A2 = 2 kg/plot, and A3 = 2.5 kg/plot. II Inorganic fertilizer dose (ANORGANIC) (N) 4 levels: N0 = 0 g/plot (control), N1 = 50 g/plo, N2 = 100 g/plot, and N3 = 150 g/plot. The results of his research from organic fertilizers were insignificant for plant height 7-28 HST, number of leaves 7-21 HST and 28 HST. The real effect is gross weight/sample, net weight/sample, gross weight/plot, and net weight/plot. Inorganic fertilizer (ANORGANIK) has a very real effect on plant height 21-18 HST, number of leaves 14 HST and 21-28 HST, leaf width, leaf length, gross weight/sample, net weight/sample, gross weight/plot, and net weight/plot. The interaction effect was very significant in plant height 7 HST, number of leaves 21, 28 HST, leaf width, leaf length, gross weight/sample, net weight/sample, gross weight/plot, and net weight/plot.